Distributed software development method representations on top of the SEMAT Kernel (2016)
Distributed software development (DSD) comprises some methods in which the stakeholders are distributed in several locations and/or time zones. Each method has its own language and term glossary. Consequently, development teams coming from different disciplines fail to adopt specific practices from other methods because the languages in which those methods are written and their glossaries are disjoint.In this M.Sc. Thesis, we propose representations of different DSD methods in a unified language (the SEMAT Essence kernel) with a unique glossary of terms to enable adopting specific practices and incorporating them into different methods. SEMAT is a standard since 2014. Representations are made on top of the SEMAT Essence kernel in order to take advantage of several universal elements for representing software engineering practices.